Exploring Next Generations for a Sustainable Future: A Systematic Literature Review on Sustainability Awareness among High School Students in Indonesia - Kurdiati, Lintang Auliya; Fathurohman*, Apit (Universitas Syiah Kuala, 2024)
Environmental damage is increasingly evident, from rising global average temperatures and melting polar ice caps to the increasing frequency of extreme weather. This study aims to conduct a literature review related to sustainability awareness among students at the high school level in Indonesia. The research method chosen in this study is a systematic literature review. Data collection is done by documenting all articles that have similar research in this research report. The articles used in this study were 11 articles published in the 20202024 period and then used as a reference for review. Based on this literature review research, several important findings were found, namely: (1) sustainability awareness can be identified in various aspects, such as instruments with the distribution of seven articles, gender differences with one article, and the existence of a sustainability awareness category covered in three articles from the total articles reviewed; (2) there are fluctuating trends in sustainability awareness research among high school students in Indonesia; and (3) the distribution of research on sustainability awareness has not been evenly distributed in all provinces in Indonesia, and so far it is still dominated by research conducted in West Java Province. These findings point to the need for equitable distribution of research in different regions to get a more comprehensive picture of the level of sustainability awareness across Indonesia.